The Role of Geographic Information Systems in Reducing Flood Risk in the BetLahem Governorate - salha, Islam R. A.; El-Mougher, Mohammed M.; El-Agha, Mohamed R. (Journal of Risk and Crisis Management, 2019)
The study aimed at extracting the valley and streamsnetwork using GIS in Bethlehem governorate and assessing the risks of floods and the most flood prone areas in the governorate in order to forecast and reduce the disaster risk related to the flood. With a description of the role of GIS in the work of hydrological analysis in order to benefit from the flood waters by identifying the optimal areas for the collection of flood waters. It showed the extraction of the map of the water streamsnetwork and the identification of river basins using GIS , and the ability of geographic information systems to assess liquidity risks, as well as the production of accurate and illustrative maps showing hazard locations, was demonstrated. And reviewed the role of GIS in the industry of opportunity and reduce the risk of disaster Through the use of floods and identify the best areas proposed for the collection of rainwater and then work on storage. It recommends the establishment of a national information bank, which will be responsible for each part of the information, to create a spatial database system that contains comprehensive maps in all areas within common standards, which will assist in disaster management and support decision-making in times of crisis and disaster using GIS.